2017
DOI: 10.1140/epjst/e2017-70054-6
|View full text |Cite
|
Sign up to set email alerts
|

LDA+DMFT approach to ordering phenomena and the structural stability of correlated materials

Abstract: Abstract. Materials with correlated electrons often respond very strongly to external or internal influences, leading to instabilities and states of matter with broken symmetry. This behavior can be studied theoretically either by evaluating the linear response characteristics, or by simulating the ordered phases of the materials under investigation. We developed the necessary tools within the dynamical mean-field theory (DMFT) to search for electronic instabilities in materials close to spin-state crossovers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 250 publications
(424 reference statements)
0
6
0
Order By: Relevance
“…As a starting point, we compute the electronic structure and phase stability of paramagnetic FeSe. To this end, we evaluate the total energy of FeSe as a function of lattice volume by employing a fully charge self-consistent (csc) DFT+DMFT scheme 30,31 and compare the result with that obtained from non-charge self-consistent (ncsc) DFT+DMFT calculations 24 (Fig. 1).…”
Section: A Phase Stability and Local Magnetic Momentsmentioning
confidence: 99%
“…As a starting point, we compute the electronic structure and phase stability of paramagnetic FeSe. To this end, we evaluate the total energy of FeSe as a function of lattice volume by employing a fully charge self-consistent (csc) DFT+DMFT scheme 30,31 and compare the result with that obtained from non-charge self-consistent (ncsc) DFT+DMFT calculations 24 (Fig. 1).…”
Section: A Phase Stability and Local Magnetic Momentsmentioning
confidence: 99%
“…The same formalism is also used to compute ground state properties such as equilibrium lattice parameters and bulk modulus. In the last decade it has been demonstrated that within the combined DFT and Dynamical Mean-Field Theory [5][6][7][8] , the so called LDA+DMFT approach 9,10 , many of the electronic ground state properties of d-metal elements, their alloys and compounds can be properly described [9][10][11][12] . This is also true in the case of palladium for which the LDA calculation of the bulk modulus turns out to overestimate the experimental value by more than 10%.…”
Section: Introductionmentioning
confidence: 99%
“…The localization properties of the Wannier functions depend on the smoothness of the Bloch eigenstates in the momentum space (for details, see Ref. [81]). Recall that the Chern number c(V v ) determines the number of singularities in any section of the complex line bundle of valence band eigenspaces V v .…”
Section: Wannier Statesmentioning
confidence: 99%